دور معلمات الروضة في تعزيز وعي الأطفال السعوديين بالأمن السيبراني في مدينة الرياض - عسيري، ذكرى بنت سعيد; عسيري، سفانة بنت حاتم (جامعة عين شمس - كلية الدراسات العليا للطفولة, 2023)
هدفت الدراسة إلى التعرف على دور معلمات الروضة في تعزيز وعي الأطفال السعوديين بالأمن السيبراني في مدينة الرياض، إضافة إلى التعرف على التحديات التي تواجه معلمات الروضة عند تعزيز وعي الأطفال بالأمن السيبراني والكشف عن وجود فروق في استجابات العينة تبعاً لمتغيرات نوع القطاع التعليمي (حكومي، أهلي)، وعدد سنوات الخبرة، وعدد الدورات التدريبية في مجال الأمن السيبراني. واعتمدت الدراسة على المنهج الوصفي المسحي، حيث أعدت الباحثتان استبانة طبقت على عينة من معلمات رياض الأطفال الحكومية والأهلية في مدينة الرياض والبالغ عددهم 350 معلمة. وتوصلت الدراسة إلى: موافقة عينة الدراسة على ممارسات معلمات الروضة في حماية الأطفال من التنمر الإلكتروني، وفى مقدمتها تعزيز شعور الثقة بالنفس لدى الطفل بتنمية مهاراته ليتقبل اختلاف الآراء لدى الآخرين. كما توصلت النتائج إلى أن أفراد العينة موافقون بشدة على ممارسات معلمات الروضة في حماية الأطفال من التحرش الإلكتروني ومن أبرزها تحذير الأطفال من عدم التواصل مع المجهولين عبر الانترنت مثل: تحذيرهم بعدم مشاركة معلوماتهم الشخصية وعقد لقاءات معهم. وأظهرت النتائج وجود تحديات تواجه معلمات الروضة مع التواصل عند تعزيز وعي الأطفال بالأمن السيبراني ومن أبرزها افتقار المنهج المقدم للطفل على مفاهيم تعزز الأمن السيبراني، وحماية الطفل من مخاطره. كما كشفت النتائج بأنه توجد فروق ذات دلالة إحصائية بين متوسط أفراد عينة الدراسة حول تعزيز وعي الأطفال بالأمن السيبرانى تعزى لمتغير نوع قطاع الروضة، وهذه الفروق لصالح مجموعة القطاع الحكومي. كما توجد فروق ذات دلالة إحصائية بين متوسط أفراد عينة الدراسة حول تعزيز وعي الأطفال بالأمن السيبراني تعزى لمتغير عدد سنوات الخبرة، وذلك لصالح مجموعة عشر سنوات أو أكثر. The study aimed to identify the practices of the kindergarten teacher to protect children from electronic bullying, as well as to identify the practices of kindergarten teachers to protect children from electronic harassment .Also, to identify the challenges facing kindergarten teachers when promoting children's awareness of cybersecurity. And to detect the differences between the samples' responses according to the variables of the type of educational sector (governmental, private), the number of years of experience, and the number of training courses in the field of cybersecurity. This study relied on the descriptive method, and the researcher prepared a questionnaire that was applied on a sample of (350) teachers from public and private kindergartens in Riyadh city .The result of this study showed that the sample agreed with the practices of kindergarten teachers in protecting children from cyberbullying, firstly enhancing the child's sense of self-confidence by developing his skills to accept differences of opinions with others .Also, this study found that the sample in strongly agreed with the practices of kindergarten teachers in protecting children from electronic harassment, the most prominent, warning children not to communicate with unknown persons via the Internet, such as: warning them not to share their personal information and to hold meetings with them. In additional, the results showed that there are challenges facing kindergarten teachers when promoting children's awareness of cybersecurity, the most prominent, the lack of concepts presented to the child in the curriculum that enhance cybersecurity and protect the child from risk. The results also revealed that there are statistically significant differences between the sample of the study about enhancing children's awareness of cybersecurity due to the type of kindergarten sector variable, and these differences are in favor of the government sector group, and there are statistically significant differences between the sample of the study about enhancing children's awareness of cybersecurity due to number of years of experience, in favor of a group of ten years or more.
Keywords: معلمو الروضة -- تعزيز الوعي -- الأمن السيبراني -- أطفال الروضة -- السعودية